The influence of nodule size on clinical efficacy of ethanol ablation and microwave ablation on cystic or predominantly cystic thyroid nodules - Ya Zhang; Xiaoqiu Chu; Yuling Liu; Yueting Zhao; Xue Han; Xin Hu; Pingping Xiang; Guofang Chen; Chao Liu; Shuhang Xu (Endocrine Connections, 2022)
Objective: To compare the efficacy and safety of ethanol ablation (EA) and m icrowave ablation (MWA) in the treatment of cystic or predominantly cyst ic thyroid nodules. Methods: Patients with cystic or predominantly cystic thyroid nodules i ntervened with EA or MWA were retrospectively enrolled and divided into EA group (n = 30) and MWA group (n = 31). The volume and volume reduction rate (VRR) of thyroid nodules before ablation, and at 3 and 12 months after ablation were compared between the two groups. The effective rate (ER) and incidence of adverse events in both grou ps were recorded. Results: The median VRR and ER at 3 months after ablation were significa ntly higher in EA group than in MWA group (81.30% vs 75.76%, P = 0.011; 76.67% (23/30) vs 51.61% (16/31), P = 0.040), while no significant difference was detected at 12 months (93.39% vs 88.78%, P = 0.141; 86.67% (26/30) vs 87.10% (27/31), P = 0.960). The median VRR of small nodules in EA group was significantly higher than that in MWA group (81.30% vs 71.18%, P = 0.006; 93.40% vs 83.14%, P = 0.032). There was no significant difference of median VRR in medium nodules at final follow-up between MWA and EA group (93.01% vs 89.68%, P = 0.482). Serious adverse events were not reported in both groups. Conclusion: EA and MWA are both effective and safe in the treatment of cyst ic or predominantly cystic thyroid nodules. EA is more cost-effective and effective than MWA for small nodules, but it requires more cycles of treatment and may pose a higher risk of postoperative pain compared with MWA.